2014
DOI: 10.3233/jad-132225
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Lifestyle Factors in Dementia: A Systematic Review of Longitudinal Observational Cohort Studies

Abstract: Broad consensus emerged on the protective role against dementia of leisure activities. Conflicting results were found for the association between dementia and putative risk factors (smoking) and protective factors (mild-to-moderate alcohol consumption, dietary antioxidants, Mediterranean diet, and living with others). However, studies varied largely in the quantification of lifestyle factors in terms of intensity, frequency and duration of exposure, and in the choice of confounders in statistical analyses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 107 publications
3
124
0
11
Order By: Relevance
“…Systematic reviews have reported that in mixed older populations, mostly without MCI, incident AD has been predicted by higher homocysteine levels, lower educational attainment, and decreased physical activity 14 . Conflicting results have been reported for the association between dementia and other putative risk factors (smoking) and protective factors (mild-to-moderate alcohol consumption, dietary antioxidants, Mediterranean diet, and living with others) 16 . Neuropsychiatric symptoms predict MCI in cognitively normal populations 15 .…”
Section: Introductionmentioning
confidence: 83%
“…Systematic reviews have reported that in mixed older populations, mostly without MCI, incident AD has been predicted by higher homocysteine levels, lower educational attainment, and decreased physical activity 14 . Conflicting results have been reported for the association between dementia and other putative risk factors (smoking) and protective factors (mild-to-moderate alcohol consumption, dietary antioxidants, Mediterranean diet, and living with others) 16 . Neuropsychiatric symptoms predict MCI in cognitively normal populations 15 .…”
Section: Introductionmentioning
confidence: 83%
“…Impaired health literacy, poorer self-management, and adverse health behaviors, such as smoking, have been linked to low income and could explain this association. From epidemiologic data, smoking appears to be a risk factor for both diabetes and dementia (38)(39)(40); however, levels of current smoking are comparable between the populations with and without diabetes and fall significantly over age 65 years (23,41). Whether prior smoking predicts dementia (or significantly differed across groups) is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…O hábito alimentar pode exercer um significante papel no desenvolvimento da doença de Alzheimer e de outras demências (Di Marco, et al, 2014).…”
Section: Insuficiência Cognitivaunclassified
“…Isso reforça a importância das medidas de prevenção para as demências, e vários estudos sugerem um possível papel da alimentação e do estilo de vida na gênese de doenças como Alzheimer e demência vascular (Di Marco, et al, 2014).…”
unclassified